2019
DOI: 10.5603/fm.a2018.0075
|View full text |Cite
|
Sign up to set email alerts
|

Aging changes in the retina of male albino rat: a histological, ultrastructural and immunohistochemical study

Abstract: Rat retinae clearly undergo age-related morphological changes such changes provide a cellular base for explanation of decreased vision in humans with aging other than reflection errors. Effect of aging was not only qualitative, but also quantitative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A study comparing young rat retinas to those of elderly and senile rats showed that with aging, the overall thickness of the retina decreases, and in senile retinas, there was a marked decrease in the thickness of the inner nuclear layer, with it only having 2-3 rows of cells. 16,17 Ocular blood flow and its regulation are altered with senescence, and elderly retinas also show, on average, a 20% decrease in macular blood flow. [18][19][20] These agerelated changes in perfusion may further exacerbate the well-described ocular perfusion abnormalities in diabetes, including impaired blood flow regulation.…”
Section: Retinal Changes With Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing young rat retinas to those of elderly and senile rats showed that with aging, the overall thickness of the retina decreases, and in senile retinas, there was a marked decrease in the thickness of the inner nuclear layer, with it only having 2-3 rows of cells. 16,17 Ocular blood flow and its regulation are altered with senescence, and elderly retinas also show, on average, a 20% decrease in macular blood flow. [18][19][20] These agerelated changes in perfusion may further exacerbate the well-described ocular perfusion abnormalities in diabetes, including impaired blood flow regulation.…”
Section: Retinal Changes With Agingmentioning
confidence: 99%
“…A study comparing young rat retinas to those of elderly and senile rats showed that with aging, the overall thickness of the retina decreases, and in senile retinas, there was a marked decrease in the thickness of the inner nuclear layer, with it only having 2–3 rows of cells. 16 , 17 …”
Section: Retinal Changes With Agingmentioning
confidence: 99%
“…Degenerative changes caused by aging may affect the sensory experience, including vision, auditory and related cognitive domains [11]. Such changes occur as a part of normal physiological processes and may be irreversible [12]. In this study, the results demonstrated a decrease in metabolic connectivity between brain regions related to sensory experience that provided a basis to explain the pathogenesis of age-associated decline in sensory experience.…”
Section: Discussionmentioning
confidence: 54%
“…Any combination of the above processes will have basic influence on the speed of tissue deterioration and cell death. Since the retina is the metabolically most active organ in the mammalian body [Graymore, 1970;Kumagai, 1999;Nivison-Smith et al, 2015]and there is very limited regenerative capacity in the CNS, it is particularly prone to damage due to aging, which has been demonstrated by several authors [Gao and Holly- field, 1992; Curcio and Drucker, 1993;Panda-Jonas et al, 1995;Kim et al, 1996;Liets et al, 2006;Aggarwal et al, 2007;Parikh et al, 2007;Freund et al, 2011;Samuel et al, 2011;Cunea et al, 2014] in several species including rats [Cano et al, 1986;Papazafiri et al, 1995;Mansour et al, 2008;Nadal-Nicolas et al, 2018a;Mohamed et al, 2019]. The majority of these papers deals with male subjects.…”
Section: Discussionmentioning
confidence: 99%